2020
DOI: 10.1098/rsos.192206
|View full text |Cite
|
Sign up to set email alerts
|

Baboon thanatology: responses of filial and non-filial group members to infants' corpses

Abstract: What do animals know of death? What can animals' responses to death tell us about the evolution of species’ minds, and the origins of humans' awareness of death and dying? A recent surge in interest in comparative thanatology may provide beginnings of answers to these questions. Here, we add to the comparative thanatology literature by reporting 12 cases of group members' responses to infants’ deaths, including 1 miscarriage and 2 stillbirths, recorded over 13 years in wild Namibian chacma baboons. Wild baboon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…Birth-related hormones cannot explain this case, although the mechanisms through which siblings bond may be a factor. Dead infant carrying by non-mothers has also been reported for geladas (Fashing et al 2011), gorillas (Warren and Williamson 2004), chimpanzees (Lonsdorf et al 2020) and baboons (Carter et al 2020), although Carter et al (2020) note that carrying by non-mothers is usually of short duration, as in our sibling vervet monkey. The learning to mother hypothesis has been proposed to explain why some non-mothers carry dead infants: behaving maternally towards even a dead infant can contribute toward gaining skills required to be a competent mother (Warren and Williamson 2004).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Birth-related hormones cannot explain this case, although the mechanisms through which siblings bond may be a factor. Dead infant carrying by non-mothers has also been reported for geladas (Fashing et al 2011), gorillas (Warren and Williamson 2004), chimpanzees (Lonsdorf et al 2020) and baboons (Carter et al 2020), although Carter et al (2020) note that carrying by non-mothers is usually of short duration, as in our sibling vervet monkey. The learning to mother hypothesis has been proposed to explain why some non-mothers carry dead infants: behaving maternally towards even a dead infant can contribute toward gaining skills required to be a competent mother (Warren and Williamson 2004).…”
Section: Discussionsupporting
confidence: 70%
“…Some researchers have also suggested that mothers may be unaware or unsure that their infants are dead, and so continue to provide maternal care (Watson and Matsuzawa 2018 ). However, behaviours directed at deceased infants that are not normally directed at live infants, such as carrying them slung across their backs (observed in chimpanzees and baboons), appear to contradict this (Biro et al 2010 ; Gonçalves and Carvalho 2019 ; Carter et al 2020 ; Lonsdorf et al 2020 ). Our observations neither support nor refute this hypothesis, although the severity of decay of Beminde’s deceased infant suggests that unawareness of death may not fully explain continued care-taking by vervet mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, differences in ranging patterns may affect duration of carriage such that larger day ranges constrain duration of carriage, as suggested by Carter et al . [ 52 ] for chacma baboons ( Papio ursinus ).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who carry their deceased infants for days, or even weeks, are bound to notice at least some of these differences. This is reflected in their adoption of carrying techniques that are never used on live infants (Biro et al 2010;Carter et al 2020;Das et al 2019;Fashing et al 2011).…”
Section: The Multiple Ways In Which Animals Can Learn About Deathmentioning
confidence: 99%